Rhetorical Dissonance in Bilingual Argumentation: (Does Arabic Rhetorical Logic Hinder or Enhance English Critical Writing?) - Dr. Mohammed Hassan Alshaikhi (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
Critical writing in English is often characterized by explicit argumentation, linear progression, and direct authorial stance, while Arabic rhetorical traditions emphasize associative logic, implicit connections, and reader-responsible meaning construction. This study explores whether this rhetorical dissonance poses a barrier for Arabic-speaking EFL learners when developing critical writing skills in English or whether their bilingual rhetorical awareness can serve as an asset for argumentation. Using a mixed-methods approach, the study analyzes Arabic and English essays from bilingual university students, employing textual analysis to identify structural differences, think-aloud protocols to capture cognitive decision-making, and interviews with bilingual academics to explore how they navigate rhetorical tension in professional writing. Findings will shed light on whether Arabic rhetorical strategies interfere with English academic writing conventions or provide a unique argumentative framework that enriches bilingual writing competence. By challenging monolingual critical writing models, this study proposes a bilingual rhetorical approach that acknowledges the dynamic interaction between Arabic and English argumentative structures, offering insights for second language writing instruction.